Sell-side analysts and corporate acquisitions: case study findings. (10th June 2020) - Andersson, Patric; Graaf, Johan; Hellman, Niclas
Abstract : Purpose: This paper aims to investigate how sell-side analysts form expectations on, analyse, and communicate the effects of corporate acquisitions. Design/methodology/approach: The paper reports on case studies of three listed firms who are frequent acquirers. The case data comprise semi-structured interviews and content analysis of analyst reports and corporate reports. Findings: The paper reports three sets of findings. First, the analysts viewed acquisitions as heterogeneous events and, therefore, also treated acquisitions differently depending on factors such as size and acquisition strategy and the perceived "authenticity" of the acquisition (i.e. whether parts of the acquisition would be more accurately described as organic growth and regular capital expenditure (CAPEX) investments). Second, the authors find that analysts struggle with analysing the effects of acquisitions at the announcement date because of a mismatch between the analysts' need of and the analysts' access to relevant information. Although clients demand evaluations of announced acquisitions, relevant accounting information is not published until much later and the information at hand only allows for cursory analyses. Finally, the authors find that the analysts' valuation models were too inflexible to fully incorporate the effects of the acquisition. In sum, the analysts, therefore, developed acquisition-driven investment cases without supporting accounting information and without converting expected acquisitions into forecasts. Originality/value: By adopting a qualitative case study research design, the paper contributes to the ongoing efforts to open the "black-box" of sell-side analyst behaviour. In particular, the unique research design focusses on effects related to specific corporate events (acquisitions) rather than analysts' everyday work.